Análise de patologias em trechos da rodovia transamazônica (BR-230), localizado no município de Itaituba Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The BR-230 highway, known as the Transamazônica, plays a crucial role in Brazil's economy by facilitating the transport of goods and the movement of people. However, as highlighted in this study, the poor state of its infrastructure has caused serious issues, such as damage to goods, increased operational costs, and a decline in logistical efficiency. The research adopted a case study approach, including a literature review and analysis of technical standards, focusing on identifying and quantifying pavement pathologies using methods such as the sand patch test. This methodology was essential for measuring the surface macrotexture of the pavement and identifying key defects, such as potholes, cracks, and ruts. These pathologies were cataloged based on the guidelines from DNIT 005 and 006, allowing for a detailed evaluation through the Individual Severity Index (ISI) and the Global Severity Index (IGG). The results indicated that many sections of the road are in an advanced state of deterioration, with several stretches classified as poor or very poor by the IGG. The main causes observed were the heavy flow of freight vehicles and the lack of regular maintenance over the years. The study emphasizes the urgent need for restoration and maintenance interventions on the BR-230, particularly in critical regions for freight transport. Proposed solutions include milling and resurfacing, improvements to the drainage system, and the implementation of a continuous maintenance schedule to extend the road's service life and ensure user safety. Additionally, future research is suggested to explore the environmental and social impacts of the BR-230's deterioration, as well as comparative studies with other highways in similar conditions.
Keywords: Rodovia; Infraestrutura; Patologias; CNPQ:: CIÊNCIAS EXATAS E DA TERRA